Preferensi Mahasiswi Dalam Memilih Hijab - Nelis Adelsi; Pardiman Pardiman; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted tofind out the preferences of female students in choosing hijab case study on studentsi Islamic University of Malang. The population in this study was 2,071 female students. The sampling technique used was Purposive Sampling and obtained 95 female students. The data collection method used is the distribution of questionnaires. The results showed that, female students tend to choose Pasminah hijab with a utility value of when compared to four other attribute levels, namely quadrilateral hijab, triangle hijab, plisket hijab, h ijab shiria, khimar hijab. Keywords: Preferences, Hijab Model, Hijab Material, Hijab Color, Hijab Motif, Hijab Price, Hijab Quality.